Neuronopathic lysosomal storage diseases: Clinical and pathologic findings. Issue 3 (24th June 2013) - Prada, Carlos E.; Grabowski, Gregory A.; Arnold, Georgianne L.; Vockley, Jerry
<x xml:space="preserve">Abstract</x> Background: The lysosomal–autophagocytic system diseases (LASDs) affect multiple body systems including the central nervous system (CNS). The progressive CNS pathology has its onset at different ages, leading to neurodegeneration and early death. Methods: Literature review provided insight into the current clinical neurological findings, phenotypic spectrum, and pathogenic mechanisms of LASDs with primary neurological involvement. Conclusions: CNS signs and symptoms are variable and related to the disease‐specific underlying pathogenesis. LAS dysfunction leads to diverse global cellular consequences in the CNS ranging from specific axonal and dendritic abnormalities to neuronal death. Pathogenic mechanisms for disease progression vary from impaired autophagy, massive storage, regional involvement, to end‐stage inflammation. Some of these features are also found in adult neurodegenerative disorders, for example, Parkinson's and Alzheimer's diseases. Lack of effective therapies is a significant unmet medical need. © 2013 Wiley Periodicals, Inc. Dev Disabil Res Rev 2013;17:226–246.